Enhancing Brain Lesions after Endovascular Treatment of Aneurysms - Cruz, J.P.; Marotta, T.; O’Kelly, C.; Holtmannspötter, M.; Saliou, G.; Willinsky, R.; Krings, T.; Agid, R. (American Journal of Neuroradiology, 2014)
SUMMARY: Complications of endovascular therapy of aneurysms mainly include aneurysm rupture and thromboembolic events. The widespread use of MR imaging for follow-up of these patients revealed various nonvascular complications such as aseptic meningitis, hydrocephalus, and perianeurysmal brain edema. We present 7 patients from 5 different institutions that developed MR imaging–enhancing brain lesions after endovascular therapy of aneurysms, detected after a median time of 63 days. The number of lesions ranged from 4–46 (median of 10.5), sized 2–20 mm, and were mostly in the same vascular territory used for access. Three patients presented with symptoms attributable to these lesions. After a median follow-up of 21.5 months, the number of lesions increased in 2, was stable in 1, decreased in 3, and disappeared in 1. The imaging and clinical characteristics suggested a foreign body reaction. We could find no correlation to a specific device, but a possible source may be the generic hydrophilic coating. EVTendovascular therapy